A low thermal conductivity / thermal expansion hafnium oxide-based thermal / environmental barrier coating and its preparation method

通过在陶瓷基复合材料上制备三层结构的氧化铪基热/环境障涂层,解决了陶瓷基复合材料在高温环境中因热失配和隔热性能不足的问题,实现了低热导率和 The low thermal expansion coefficient significantly improves the service stability and anti-water oxygen corrosion performance of high-temperature components.

CN116589304BActive Publication Date: 2024-12-27AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310470648.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2024-12-27
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

In high-temperature environment, ceramic matrix composite materials cause interface oxidation and peeling due to thermal mismatch between the thermal barrier surface layer and EBC and CMC, and the thermal insulation performance of the surface layer material is insufficient, resulting in softening of Si bonding layer and cracking of coatings, limiting the Reliability and stability of thermal/environmental barrier coatings at higher temperature applications.

Method used

Using a three-layer structure hafnium oxide-based thermal/environmental barrier coating, including HfO2-Si bonding layer, Yb2Si2O7 environmental barrier layer, and β-LiAlSiO4 and RE2O3 modified HfO2 thermal barrier surface layer, it was prepared and vacuumed by atmospheric plasma spraying technology. Heat treatment, the thickness and composition ratio of each layer are controlled to achieve low thermal conductivity and low thermal expansion coefficient.

Benefits of technology

Under 1500℃, the thermal shock life of the coating shall not be less than 500 times, and shall not be less than 200 hours in 1500℃, 90% H2O-10% O2 environment, which significantly improves the service of high-temperature components of ceramic matrix composite materials Stability and anti-hydrogen corrosion properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116589304B_ABST
    Figure CN116589304B_ABST
Patent Text Reader

Abstract

The present invention relates to a hafnium oxide-based thermal environmental barrier coating with low thermal conductivity / thermal expansion and a preparation method thereof. The thermal / environmental barrier coating includes, from the substrate to the outside, a HfO2-Si bonding layer with a thickness of 50 to 100 μm, a Yb2Si2O7 environmental barrier layer with a thickness of 100 to 150 μm, and a β-LiAlSiO4, RE2O3-modified HfO2 thermal barrier surface layer with a thickness of 150 to 200 μm. An atmospheric plasma spraying process is used to sequentially prepare a bonding layer, an environmental barrier layer, and a thermal barrier surface layer on the surface of a pretreated ceramic-based composite material, and the prepared thermal / environmental barrier coating is subjected to vacuum heat treatment. The thermal expansion coefficient gradient of the bonding layer, the environmental barrier layer, and the thermal barrier surface layer of the thermal / environmental barrier coating of the present invention increases, and the thermal barrier surface layer has the characteristics of low thermal conductivity and low thermal expansion coefficient at the same time, which can greatly improve the service life of such thermal / environmental barrier coating in the engine gas environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thermal barrier / environmental barrier integrated coatings, and in particular relates to a hafnium oxide-based thermal / environmental barrier coating with low thermal conductivity / thermal expansion and a preparation method thereof. Background Art

[0002] Ceramic matrix composites are ideal materials for high-temperature components of high-performance aircraft engines. Preparing thermal / environmental barrier coatings on their surfaces is an important way to improve their service reliability and stability in complex high-temperature gas environments. However, in actual service, on the one hand, through cracks occur between the thermal barrier surface layer and the EBC and CMC due to thermal mismatch, resulting in interface oxidation and spalling; on the other hand, the surface material has insufficient thermal insulation performance, resulting in softening or even melting of the Si bonding layer, causing cracking and failure of the coating. At present, the inverse correlation between the "low thermal conductivity" and "high thermal expansion coefficient" of the thermal barrier surface material is the main reason that limits the application of thermal / environmental barrier coatings at higher temperatures.

[0003] Domestic and foreign scholars have mainly solved the above problems by: (1) adding a buffer layer to form a multi-layer gradient thermal / environmental barrier coating structure; (2) designing multi-component / high-entropy rare earth silicate materials. The former can alleviate the interlayer thermal mismatch problem to a certain extent, but during long-term thermal service, the interface chemical stability between the layers is reduced due to element diffusion, causing the coating performance to decline sharply. In addition, the preparation process of this method is relatively complex, which significantly increases the manufacturing cost. Most of the research on the latter is based on bulk materials, and the research on the typical thermal physical properties of high-entropy EBC coatings is relatively limited. In fact, due to different preparation methods, the coating composition and structure are relatively dispersed, and the comprehensive performance of high-entropy coatings needs further study.

[0004] Therefore, the development of a new type of thermal / environmental barrier coating with low thermal conductivity and low thermal expansion coefficient and its preparation technology are of great significance to improving the service temperature and stability of high-temperature components of ceramic-based composite materials and reducing the overall weight of aircraft engines. Summary of the invention

[0005] In view of the above-mentioned situation of the prior art, the purpose of the present invention is to provide a thermal / environmental barrier coating and a preparation method thereof having both low thermal conductivity and low thermal expansion coefficient in the range of room temperature to 1500°C, so that the thermal / environmental barrier coating has excellent thermal shock resistance and water-oxygen corrosion resistance in the engine service environment, thereby improving the service stability and reliability of high-temperature components of ceramic-based composite materials.

[0006] To achieve the above-mentioned purpose, on the one hand, the present invention provides a hafnium oxide-based thermal / environmental barrier coating with low thermal conductivity / thermal expansion, wherein the coating has a three-layer structure, and comprises, from the inside to the outside, a HfO2-Si bonding layer, a Yb2Si2O7 environmental barrier layer and a β-LiAlSiO4, RE2O3 modified HfO2 thermal barrier surface layer, wherein in the HfO2-Si bonding layer, the mass ratio of HfO2 to Si is 1:5 to 5:1, in the β-LiAlSiO4, RE2O3 modified HfO2 thermal barrier surface layer, the mass ratio of β-LiAlSiO4, RE2O3 and HfO2 is 5 to 30:5 to 30:40 to 90, and the RE is one or more of Yb, Y, Gd, Sm and Nd.

[0007] The thickness of the HfO2-Si bonding layer is 50-100 μm; the thickness of the Yb2Si2O7 environmental barrier layer is 100-150 μm; the thickness of the β-LiAlSiO4 and RE2O3 modified HfO2 thermal barrier surface layer is 150-200 μm.

[0008] Preferably, in the HfO2-Si bonding layer, the mass ratio of HfO2 to Si is 1:5 to 1:2.

[0009] Preferably, in the β-LiAlSiO4, RE2O3 modified HfO2 thermal barrier layer, the mass ratio of β-LiAlSiO4, RE2O3 and HfO2 is 15-30:10-20:50-75.

[0010] On the other hand, a method for preparing the hafnium oxide-based thermal / environmental barrier coating with low thermal conductivity / thermal expansion as described above is provided, the preparation method comprising the following steps:

[0011] S1: pre-treating the ceramic matrix composite matrix;

[0012] S2: Using atmospheric plasma spraying technology to sequentially prepare HfO2-Si bonding layer, Yb2Si2O7 environmental barrier layer and β-LiAlSiO4 and RE2O3 modified HfO2 thermal barrier surface layer on the surface of ceramic matrix composite material matrix;

[0013] S3: performing vacuum heat treatment on the prepared coating.

[0014] Wherein: the step S1 is specifically as follows:

[0015] S101: placing the ceramic-based composite material substrate in acetone for ultrasonic cleaning for 10 to 30 minutes, and then placing it in an oven for drying for 10 to 20 minutes at a temperature of 100 to 120° C.;

[0016] S102: sandblasting the cleaned substrate, wherein the sandblasting sand particles are 100-200 mesh quartz sand, the sandblasting pressure is 1-3 bar, and the sandblasting time is 10-30 seconds;

[0017] S103: The composite material matrix is ​​heated by the plasma flame flow so that the surface temperature thereof reaches 500-800°C.

[0018] Preferably, in the process of preparing the HfO2-Si bonding layer, argon and hydrogen are used as plasma, the flow rate of argon is 40-60 L / min, the flow rate of hydrogen is 6-15 L / min, the spraying distance is 60-120 mm, the spraying current is 300-600 A, the powder feeding rate is 5-25%, and the powder particle size of HfO2-Si is 15-80 μm.

[0019] Preferably, in the process of preparing the Yb2Si2O7 environmental barrier layer, argon and hydrogen are used as plasma, the flow rate of argon is 40-60L / min, the flow rate of hydrogen is 6-15L / min, the spraying distance is 100-150mm, the spraying current is 500-1000A, the powder feeding rate is 5-25%, and the Yb2Si2O7 powder particle size is 15-80μm.

[0020] Preferably, in the process of preparing the β-LiAlSiO4 and RE2O3 modified HfO2 thermal barrier layer, argon and hydrogen are used as plasma, the flow rate of argon is 40-60L / min, the flow rate of hydrogen is 6-15L / min, the spraying distance is 100-150mm, the spraying current is 500-1000A, the powder feeding rate is 5-25%, and the powder particle size of β-LiAlSiO4 and RE2O3 modified HfO2 is 15-50μm.

[0021] Preferably, the vacuum heat treatment parameters are: heat treatment temperature is 1000-1200°C, time is 4-6 hours, vacuum degree is 10 -3 Pa, that is, as long as the vacuum degree reaches 10 -3 Pa level is enough.

[0022] The hafnium oxide-based thermal / environmental barrier coating prepared by the present invention has a thermal shock life of not less than 500 times under the conditions of 1500°C, 5 minutes of heat preservation and 5 minutes of air cooling; and a coating life of not less than 200 hours under the conditions of 1500°C, 90% H2O-10% O2 and 1atm. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings of the present invention are provided for illustrative purposes only, and the proportions and sizes of the layers in the drawings may not necessarily be consistent with the actual products.

[0024] Figure 1is a schematic cross-sectional structure diagram of a thermal / environmental barrier coating prepared on the surface of a ceramic-based composite material according to an embodiment of the present invention;

[0025] Figure 2 is a flow chart of a method for preparing a thermal / environmental barrier coating on a surface of a ceramic-based composite material according to an embodiment of the present invention;

[0026] Figure 3 is the cross-sectional morphology of the HfO2-Si bonding layer in the embodiment of the present invention;

[0027] Figure 4 The present invention shows the surface morphology of a thermal / environmental barrier coating prepared on the surface of a ceramic-based composite material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] The features of various aspects of the embodiments of the present invention will be described in detail below. In the detailed description below, many specific details are proposed to fully understand the present invention. However, it is obvious to those skilled in the art that the present invention can also be implemented without these specific details. The following description of the embodiments is only for a better understanding of the present invention by illustrating examples of the present invention. The present invention is not limited to any specific settings and methods provided below, but covers all product structures, any improvements, replacements, etc. of the methods covered without departing from the spirit of the present invention. In the various drawings and the following description, known structures and technologies are not shown to avoid unnecessary ambiguity of the present invention.

[0030] Figure 1 The cross-sectional structure diagram of the thermal / environmental barrier coating prepared on the surface of the ceramic-based composite material of the present invention. The thermal / environmental barrier coating includes, from the ceramic-based composite material substrate 1 to the outside, a HfO2-Si bonding layer 2, a Yb2Si2O7 environmental barrier layer 3, β-LiAlSiO4, and a RE2O3-modified HfO2 thermal barrier surface layer 4.

[0031] In the HfO2-Si bonding layer, the mass ratio of HfO2 to Si is 1:5 to 5:1, preferably 1:5 to 1:2. In addition, in the β-LiAlSiO4 and RE2O3 modified HfO2 thermal barrier layer, RE is one or more of Yb, Y, Gd, Sm and Nd, and the mass ratio of β-LiAlSiO4, RE2O3 and HfO2 is 5 to 30:5 to 30:40 to 90, preferably 15 to 30:10 to 20:50 to 75. The inventors have found that when the masses of β-LiAlSiO4, RE2O3 and HfO2 are used in combination according to the above-mentioned components, the obtained thermal barrier layer has low thermal conductivity, low thermal expansion coefficient and good high temperature stability.

[0032] Figure 2 It is a flow chart of a method for preparing a thermal / environmental barrier coating on the surface of a ceramic-based composite material in one embodiment of the present invention.

[0033] The method comprises the following steps:

[0034] S1: pre-treating the ceramic matrix composite matrix;

[0035] S101, placing the ceramic-based composite material substrate in acetone for ultrasonic cleaning for 10 to 30 minutes, and then placing it in an oven for drying for 10 to 20 minutes at a temperature of 100 to 120° C.;

[0036] S102, performing sandblasting on the cleaned substrate, wherein the sandblasting sand particles are 100-200 mesh quartz sand, the sandblasting pressure is 1-3 bar, and the sandblasting time is 10-30 seconds;

[0037] S103, heating the composite material matrix by plasma flame flow so that its surface temperature reaches 500-800°C.

[0038] S2: Using atmospheric plasma spraying technology to sequentially prepare HfO2-Si bonding layer, Yb2Si2O7 environmental barrier layer and β-LiAlSiO4 and RE2O3 modified HfO2 thermal barrier surface layer on the substrate surface;

[0039] The powder particle size of S201 and HfO2-Si is 15-80μm, argon and hydrogen are used as plasma, the flow rate of argon is 40-60L / min, the flow rate of hydrogen is 6-15L / min, the spraying distance is 60-120mm, the spraying current is 300-600A, and the powder feeding rate is 5-25%.

[0040] The particle size of S202 and Yb2Si2O7 powders is 15-80μm, argon and hydrogen are used as plasma, the flow rate of argon is 40-60L / min, the flow rate of hydrogen is 6-15L / min, the spraying distance is 100-150mm, the spraying current is 500-1000A, and the powder feeding rate is 5-25%.

[0041] The powder particle size of S203, β-LiAlSiO4, and RE2O3 modified HfO2 is 15-50μm. Argon and hydrogen are used as plasma, the flow rate of argon is 40-60L / min, the flow rate of hydrogen is 6-15L / min, the spraying distance is 100-150mm, the spraying current is 500-1000A, and the powder feeding rate is 5-25%.

[0042] S3: performing vacuum heat treatment on the as-prepared thermal / environmental barrier coating.

[0043] The heat treatment temperature is 1000-1200℃, the time is 4-6h, and the vacuum degree is 10 -3 Pa.

[0044] Example 1

[0045] (1) Preparation of SiC f The / SiC ceramic composite matrix specimen, with a size of 20 mm × 10 mm × 3 mm, was ultrasonically cleaned with acetone for 20 min and then dried in an oven at 110 °C for 20 min.

[0046] (2) For SiC f The SiC substrate was sandblasted before spraying, with 150-mesh quartz sand, 2 bar pressure and 20 s time.

[0047] (3) SiC f The SiC substrate is installed on the automatic working table of the atmospheric plasma spraying equipment and is heated by the plasma flame flow to a surface temperature of 700°C.

[0048] (4) The powder particle size of HfO2-Si after spray granulation is selected to be 15-80 μm, the powder particle size of Yb2Si2O7 is 15-80 μm, and the powder particle size of β-LiAlSiO4 and Y2O3 modified HfO2 is 15-50 μm. The powder morphology after granulation is porous spherical powder. The above three powders are added to the powder feeder of the atmospheric plasma spraying equipment in sequence.

[0049] The HfO2-Si, Yb2Si2O7, β-LiAlSiO4, RE2O3 and HfO2 powders used in the present invention can all be obtained from the market, and their preparation processes are also well known to those skilled in the art. For example, the HfO2-Si powder and Yb2Si2O7 powder in this embodiment are purchased from Hunan Zhaoyi Thermal Spraying Material Co., Ltd., and the mass ratio of HfO2 to Si in the HfO2-Si powder is 1:4. β-LiAlSiO4 powder is purchased from Changsha College. In addition, although the preparation methods of β-LiAlSiO4 and Y2O3 modified HfO2 powders are illustrated below for the sake of clarity, such preparation methods are also well known to those skilled in the art, so that it is within the capabilities of those skilled in the art to prepare the desired β-LiAlSiO4 and Y2O3 modified HfO2 powders using raw material powders by similar preparation methods.

[0050] The preparation method of β-LiAlSiO4, Y2O3 modified HfO2 powder is as follows:

[0051] (a) Y2O3 and HfO2 were mixed in a molar ratio of 0.2:0.8 and then wet-milled for 6 h at a speed of 300 r / min. -1 The ball-milled slurry was placed in an 80°C drying oven for 5 hours, manually ground, and passed through a 200-mesh sieve. The resulting powder was sintered at 1500°C for 5 hours;

[0052] (b) β-LiAlSiO4 powder and Y2O3-HfO2 powder were mixed in a weight ratio of 1:4 and then wet-milled for 4 h at a speed of 200 r / min. -1 , Place the ball-milled slurry in a drying oven at 80°C and dry for 5 hours;

[0053] (c) The dried powder is spray granulated, with the following specific parameters: inlet temperature 200°C, outlet temperature 100°C, and PVA as the binder; the spray granulated powder is sintered at 1200°C for 4 hours to remove the organic binder layer.

[0054] (5) Using atmospheric plasma spraying method on SiC f / SiC substrate surface preparation HfO2-Si bonding layer, adjust the process parameters: argon flow rate of 40L / min, hydrogen flow rate of 8L / min, spraying distance of 80mm, spraying current of 350A, powder feeding rate of 25%, to obtain a bonding layer with a thickness of 50μm, the cross-sectional morphology is as follows Figure 3 shown.

[0055] (6) An atmospheric plasma spraying method was used to prepare a Yb2Si2O7 environmental barrier layer on the surface of the HfO2-Si bonding layer. The process parameters were adjusted as follows: an argon flow rate of 50 L / min, a hydrogen flow rate of 10 L / min, a spraying distance of 120 mm, a spraying current of 550 A, and a powder feeding rate of 5-25%, to obtain a Yb2Si2O7 environmental barrier layer with a thickness of 100 μm.

[0056] (7) The β-LiAlSiO4 and Y2O3 modified HfO2 thermal barrier surface layer was prepared on the surface of the Yb2Si2O7 environmental barrier layer by atmospheric plasma spraying. The process parameters were adjusted as follows: the flow rate of argon was 50 L / min, the flow rate of hydrogen was 8 L / min, the spraying distance was 120 mm, the spraying current was 600 A, and the powder feeding rate was 25%. The β-LiAlSiO4 and Y2O3 modified HfO2 thermal barrier surface layer with a thickness of 200 μm was obtained.

[0057] (8) The prepared coating was subjected to vacuum heat treatment, and the process parameters were adjusted as follows: temperature 1150 °C, time 6 h, vacuum degree 5 × 10 -3 Pa.

[0058] The surface morphology of the thermal / environmental barrier coating in Example 1 is as follows: Figure 4 As shown, the thermal shock resistance test is carried out on it:

[0059] The thermal shock resistance test is performed under the conditions of 1500°C, 5 minutes of heat preservation, and 5 minutes of air cooling until the coating peels off obviously (peeling area is greater than 10%), which is defined as failure. The results show that the thermal shock resistance life of the thermal / environmental barrier coating in this embodiment is 506 cycles.

[0060] Example 2

[0061] The process of Example 2 is basically the same as that of Example 1, except that:

[0062] In (4), the mass ratio of HfO2 and Si in the HfO2-Si powder is 1:3, and the mass ratio of β-LiAlSiO4 and Y2O3 / Yb2O3 modified HfO2 in the β-LiAlSiO4 and Y2O3 / Yb2O3 modified HfO2 powders is 15:85.

[0063] In (6), the thickness of the Yb2Si2O7 environmental barrier layer is 150 μm.

[0064] In (8), the heat treatment temperature is 1200°C and the time is 4 h.

[0065] The thermal / environmental barrier coating in Example 2 was tested for high temperature water-oxygen corrosion performance:

[0066] The water-oxygen corrosion resistance test is conducted under 1500°C, 90% H2O-10% O2, 1atm environment until the coating peels off obviously (peeling area is greater than 10%), which is defined as failure. The results show that the water-oxygen corrosion resistance life of the thermal / environmental barrier coating in this embodiment is 208 hours.

[0067] Example 3

[0068] In addition, in order to illustrate the effect of different mass ratios of β-LiAlSiO4, Y2O3 and HfO2 in β-LiAlSiO4 and Y2O3 modified HfO2 thermal barrier layer on the thermal conductivity and thermal expansion behavior of thermal barrier layer materials, the SiC f The β-LiAlSiO4 and Y2O3 modified HfO2 thermal barrier layer is directly prepared on the surface of the / SiC ceramic composite material matrix. The specific steps are as follows:

[0069] (1) Preparation of SiC f The / SiC ceramic composite matrix specimen, with a size of 20 mm × 10 mm × 3 mm, was ultrasonically cleaned with acetone for 20 min and then dried in an oven at 110 °C for 20 min.

[0070] (2) For SiC f The SiC substrate was sandblasted before spraying, with 150-mesh quartz sand, 2 bar pressure and 20 s time.

[0071] (3) SiC f The SiC substrate is installed on the automatic working table of the atmospheric plasma spraying equipment and is heated by the plasma flame flow to a surface temperature of 600°C.

[0072] (4) The particle size of the β-LiAlSiO4 and Y2O3 modified HfO2 powders after spray granulation is selected to be 15 to 50 μm. The powder morphology after granulation is porous spherical powder, and the above powder is placed in the powder feeder of the atmospheric plasma spraying equipment. Among them, the mass ratios of β-LiAlSiO4, Y2O3 and HfO2 in the β-LiAlSiO4 and Y2O3 modified HfO2 powders are 5:5:90, 10:10:80, 15:10:75, 20:15:65, 20:20:60, 30:20:50, and 30:30:40, respectively.

[0073] (5) Using atmospheric plasma spraying method on SiC f / SiC substrate surface preparation β-LiAlSiO4, Y2O3 modified HfO2 thermal barrier layer, adjust the process parameters: argon flow rate of 50L / min, hydrogen flow rate of 8L / min, spraying distance of 120mm, spraying current of 600A, powder feeding rate of 25%. Get the thickness of 800μm β-LiAlSiO4, Y2O3 modified HfO2 thermal barrier layer.

[0074] The thermal expansion coefficient and thermal conductivity of the thermal barrier surface layer were tested, and the results are shown in Table 1. It can be seen that the mass ratio of β-LiAlSiO4, Y2O3 and HfO2 in the β-LiAlSiO4, Y2O3 modified HfO2 thermal barrier surface layer is 5-30:5-30:40-90, preferably 15-30:10-20:50-80. When β-LiAlSiO4, Y2O3 and HfO2 are used in combination according to the above components, the obtained thermal barrier surface layer has both low thermal conductivity and low thermal expansion coefficient, and has better high temperature protection effect.

[0075] Table 1 Performance indicators of HfO2 coatings modified with different weight ratios of β-LiAlSiO4 and Y2O3 in Example 3

[0076]

[0077]

[0078] Comparative Example 1

[0079] The process of Comparative Example 1 is basically the same as that of Example 1, except that:

[0080] In (4), the particle size of the Y2O3-modified HfO2 powder after spray granulation is selected to be 15 to 50 μm. The mass ratio of Y2O3 to HfO2 in the Y2O3-modified HfO2 powder is 20:80.

[0081] In (7), an atmospheric plasma spraying method is used to prepare a Y2O3-modified HfO2 thermal barrier surface layer on the surface of the Yb2Si2O7 environmental barrier layer, thereby obtaining a Y2O3-modified HfO2 thermal barrier surface layer with a thickness of 200 μm.

[0082] The thermal shock resistance of the thermal / environmental barrier coating prepared in this comparative example was tested by the same testing method as in Example 1, and the thermal shock resistance life was 275 cycles.

[0083] Comparative Example 2

[0084] The process of Comparative Example 2 is basically the same as that of Example 1, except that:

[0085] In (4), the particle size of the β-LiAlSiO4 modified HfO2 powder after spray granulation is selected to be 15 to 50 μm. The mass ratio of β-LiAlSiO4 to HfO2 in the β-LiAlSiO4 modified HfO2 powder is 20:80.

[0086] In (7), a β-LiAlSiO4 modified HfO2 thermal barrier surface layer was prepared on the surface of the Yb2Si2O7 environmental barrier layer by an atmospheric plasma spraying method, thereby obtaining a Y2O3 modified HfO2 thermal barrier surface layer with a thickness of 200 μm.

[0087] The water-oxygen corrosion resistance of the thermal / environmental barrier coating prepared in this comparative example was tested using the same testing method as in Example 2, and the water-oxygen corrosion resistance life of the coating was 72 hours.

[0088] Comparative Example 3

[0089] The process of Comparative Example 2 is basically the same as that of Example 1, except that:

[0090] In (4), the particle size of Si powder after spray granulation is selected to be 15 to 80 μm.

[0091] In (5), atmospheric plasma spraying is used to deposit SiC f A Si bonding layer was prepared on the surface of the / SiC substrate to obtain a bonding layer with a thickness of 75 μm.

[0092] The water-oxygen corrosion resistance of the thermal / environmental barrier coating prepared in this comparative example was tested using the same testing method as in Example 2, and the water-oxygen corrosion resistance life of the coating was 123 hours.

[0093] The present invention has the following beneficial effects:

[0094] (1) The HfO2-Si bonding layer of the thermal / environmental barrier coating of the present invention has a high interfacial bonding strength with the ceramic-based composite material matrix, has excellent strength and fracture toughness, and exhibits good oxidation resistance and creep properties in the range of 1350°C to 1400°C.

[0095] (2) The thermal / environmental barrier coating β-LiAlSiO4 and RE2O3 modified HfO2 thermal barrier surface layer described in the present invention, RE2O3 doping introduces oxygen vacancies and causes lattice distortion, which can effectively reduce the thermal conductivity of the HfO2 material; the addition of negative expansion characteristic β-LiAlSiO4 can reduce the thermal expansion coefficient of RE2O3-HfO2, thereby increasing the thermal adaptability of the thermal barrier surface layer to the environmental barrier layer and the bonding layer.

[0096] (3) The thermal expansion coefficients of the HfO2-Si bonding layer, the Yb2Si2O7 environmental barrier layer and the β-LiAlSiO4 and RE2O3 modified HfO2 thermal barrier surface layer in the thermal / environmental barrier coating described in the present invention show a gradient increasing trend, which effectively reduces the thermal cycling stress of the coating during service and significantly improves the service life of the thermal / environmental barrier coating.

[0097] (4) By controlling the mass percentage of β-LiAlSiO4, RE2O3 and HfO2 in the coating, the thermal conductivity and thermal expansion coefficient of the thermal barrier surface layer can be precisely controlled. Through the synergistic effect of the three components, the optimal high-temperature stability, thermal shock resistance and water-oxygen corrosion resistance are achieved.

Claims

1. A low thermal conductivity / thermal expansion hafnium oxide-based thermal / environmental barrier coating, characterized in that: The coating includes, from the inside to the outside, a HfO2-Si bonding layer, a Yb2Si2O7 environmental barrier layer, and a β-LiAlSiO4 and RE2O3 modified HfO2 thermal barrier surface layer. In the HfO2-Si bonding layer, the mass ratio of HfO2 to Si is 1:5 to 5:

1. In the β-LiAlSiO4 and RE2O3 modified HfO2 thermal barrier layer, the mass ratio of β-LiAlSiO4, RE2O3 and HfO2 is 5-30:5-30:40-90, and The RE is one or more of Yb, Y, Gd, Sm and Nd.

2. The hafnium oxide-based thermal / environmental barrier coating according to claim 1, wherein the thickness of the HfO2-Si bonding layer is 50 to 100 μm; the thickness of the Yb2Si2O7 environmental barrier layer is 100 to 150 μm; and the thickness of the β-LiAlSiO4, RE2O3 modified HfO2 thermal barrier surface layer is 150 to 200 μm.

3. The hafnium oxide-based thermal / environmental barrier coating according to claim 1, wherein in the HfO2-Si bonding layer, the mass ratio of HfO2 to Si is 1:5 to 1:

2.

4. The hafnium oxide-based thermal / environmental barrier coating according to claim 1, wherein in the β-LiAlSiO4, RE2O3-modified HfO2 thermal barrier surface layer, the mass ratio of β-LiAlSiO4, RE2O3 and HfO2 is 15-30:10-20:50-75.

5. A method for preparing a hafnium oxide-based thermal / environmental barrier coating according to claim 1, characterized in that The following steps are involved: S1: pre-treating the ceramic matrix composite matrix; S2: The HfO2-Si bonding layer, the Yb2Si2O7 environmental barrier layer and the β-LiAlSiO4 and RE2O3 modified HfO2 thermal barrier surface layer are sequentially prepared on the surface of the ceramic matrix composite material by atmospheric plasma spraying process; S3: performing vacuum heat treatment on the prepared coating.

6. The method according to claim 5, wherein the step S1 comprises: S101: placing the ceramic-based composite material substrate in acetone for ultrasonic cleaning for 10 to 30 minutes, and then drying it at 100 to 120° C. for 10 to 20 minutes; S102: sandblasting the cleaned ceramic-based composite material substrate, wherein the sandblasting sand particles are 100-200 mesh quartz sand, the sandblasting pressure is 1-3 bar, and the sandblasting time is 10-30 seconds; S103: heating the ceramic-based composite material matrix by means of a plasma flame flow, so that the surface temperature thereof reaches 500 to 800°C.

7. The method according to claim 5, wherein when preparing the HfO2-Si bonding layer, argon and hydrogen are used as plasma, the flow rate of argon is 40-60 L / min, the flow rate of hydrogen is 6-15 L / min, the spraying distance is 60-120 mm, the spraying current is 300-600 A, the powder feeding rate is 5-25%, and the powder particle size of HfO2-Si is 15-80 μm.

8. The method according to claim 5, wherein when preparing the Yb2Si2O7 environmental barrier layer, argon and hydrogen are used as plasma, the flow rate of argon is 40-60 L / min, the flow rate of hydrogen is 6-15 L / min, the spraying distance is 100-150 mm, the spraying current is 500-1000 A, the powder feeding rate is 5-25%, and the particle size of the Yb2Si2O7 powder is 15-80 μm.

9. The method according to claim 5, wherein when preparing the β-LiAlSiO4, RE2O3 modified HfO2 thermal barrier surface layer, argon and hydrogen are used as plasma, the flow rate of argon is 40-60L / min, the flow rate of hydrogen is 6-15L / min, the spraying distance is 100-150mm, the spraying current is 500-1000A, the powder feeding rate is 5-25%, and the powder particle size of β-LiAlSiO4, RE2O3 modified HfO2 is 15-50μm.

10. The method according to claim 5, wherein in step S3, the heat treatment temperature is 1000-1200°C, the time is 4-6 hours, and the vacuum degree is 10 -3 Pa level.

Citation Information

Patent Citations

  • Transient state ultrahigh temperature resisting heat barrier coat ceramic layer material and preparation method thereof

    CN101265561A

  • Erosion and CMAS resistant coating for protecting EBC and cmc layers and thermal spray coating method

    CN111417740A

  • Silicon-based composite coating, preparation method and application thereof and aero-engine

    CN112279682A

  • Thermal-environmental barrier coating and preparation method and application thereof

    CN113278909A

  • Self-healing environmental barrier coating for ceramic-based composite material and preparation method of self-healing environmental barrier coating

    CN113307660A